GENETIC STABILITY EVALUATION OF QUERCUS SUBER L . SOMATIC EMBRYOGENESIS BY RAPD ANALYSIS - Fernandes, Pedro; Costa, Armando; Rocha, Cristina; Santos, Conceição; Al, E. T. (Pakistan Journal of Botany, 2011)
A reliable protocol for adult Quercus suber L. somatic embryogenesis (SE) was developed recently. To evaluate the potential use of this protocol in cork oak forest breeding programs, it is essential to guarantee somatic embryos/emblings genetic stability. Random Amplification of Polymorphic DNA (RAPD) is currently used to assess somaclonal variation providing information on genetic variability of the micropropagation process. In this work, SE was induced from adult trees by growing leaf explants on MS medium supplemented with 2,4-D and zeatin. Embling conversion took place on MS medium without growth regulators. DNA from donor tree, somatic embryos and emblings was used to assess genetic variability by RAPD fingerprinting. Fourteen primers produced 165 genetic loci with high quality and reproducibility. Despite somatic embryos originated some poor quality PCR-profiles, replicable and excellent fingerprints were obtained for both donor plant and embling. Results presented no differences among regenerated emblings and donor plant. Hence, the SE protocol used did not induce, up to moment, any genetic variability, confirming data previously obtained with other molecular/genetic techniques, supporting that this protocol may be used to provide true-to-type plants from important forestry species.
Keywords: genetic stability; Quercus suber (voyant); RAPD; Somatic embryogenesis